Corrective Power Network Reconfiguration for Eliminating Transmission Lines Overload - Zhang, Yingling; Xu, Zhengqi; Kuang, Jing; Han, Ye; Zheng, Liwei; Guo, Ruipeng (2020 IEEE 1st China International Youth Conference on Electrical Engineering (CIYCEE), 2020)
The power flow of transmission lines may be overloaded when contingencies occur. To solve this problem effectively, this paper proposes a two-staged optimization model, which considers spinning reserve resources and network adjustment. Firstly, a DC power flow based mathematical model of network reconfiguration is introduced to obtain an approximate optimal solution. Then an AC power flow based mathematical model of network reconfiguration is introduced, and the obtained approximate optimal solution is used as an initial state. The proposed model is a mixed integer nonlinear programming (MINLP) model, because it considers the AC power flow constraints and introduces binary integer variables. The branch and bound method and the primal dual interior point method are used to solve the MINLP problem. Finally, the correctness and effectiveness of the proposed methods are verified by simulations on Fujian transmission grids.